Ethylene Regulates Energy-Dependent Non-Photochemical Quenching in Arabidopsis through Repression of the Xanthophyll Cycle - Chen, Zhong (PLoS One, 2015)
Energy-dependent (qE) non-photochemical quenching (NPQ) thermally dissipates excess absorbed light energy as a protective mechanism to prevent the over reduction of photosystem II and the generation of reactive oxygen species (ROS). The xanthophyll cycle, induced when the level of absorbed light energy exceeds the capacity of photochemistry, contributes to qE. In this work, we show that ethylene regulates the xanthophyll cycle in Arabidopsis. Analysis of eto1-1, exhibiting increased ethylene production, and ctr1-3, exhibiting constitutive ethylene response, revealed defects in NPQ resulting from impaired de-epoxidation of violaxanthin by violaxanthin de-epoxidase (VDE) encoded by NPQ1. Elevated ethylene signaling reduced the level of active VDE through decreased NPQ1 promoter activity and impaired VDE activation resulting from a lower transthylakoid membrane pH gradient. Increasing the concentration of CO(2) partially corrected the ethylene-mediated defects in NPQ and photosynthesis, indicating that changes in ethylene signaling affect stromal CO(2) solubility. Increasing VDE expression in eto1-1 and ctr1-3 restored light-activated de-epoxidation and qE, reduced superoxide production and reduced photoinhibition. Restoring VDE activity significantly reversed the small growth phenotype of eto1-1 and ctr1-3 without altering ethylene production or ethylene responses. Our results demonstrate that ethylene increases ROS production and photosensitivity in response to high light and the associated reduced plant stature is partially reversed by increasing VDE activity.